Solo leveling. 13 - Ch'ugong; Ch'ugong; h-goon (Anime creator) (Ize Press, 2025)
"Curtains rise on the final battle between hunters and monarchs as the King of Dragons finally arrives on Earth. The fate of all mankind rests in the hands of Jinwoo Sung, the new Shadow Monarch-but as the fierce war drags on, will there be a world left to save?"--yenpress.com.